Local History of Indonesia as a Form Rise of Nationalism - Dahnial, Irfan (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
Local history reminds us that life is always changing, including changes at the local level, human attitudes towards change are very much influenced by the horizons they have. The uniqueness of the history that exists in the environment can also be considered as part of local wisdom, so that we can also learn from the symbolic aspects which are generally full of local historical events. And in a prophetic dimension, local history that is developed and packaged in a positive thinking dimension can be a means of a healing and self-development process. the research objective is to maintain and arouse a sense of nationalism through local history that exists in each region. This research method uses the literature review method, namely a description of the theory, findings and other research materials obtained from reference materials to be used as the basis for research activities in formulating a clear frame of mind from the formulation of the problems to be compiled and studied. The final goal of a literature review is to get an idea of what other people have done before, literature review or also known as literature review is the first step to gathering relevant information.